Innovation Quinary and n‐Value toward Fuzzy Logic QCA Cell Design. Issue 2 (7th December 2021) - Akbari‐Hasanjani, Reza; Sabbaghi‐Nadooshan, Reza
Abstract: Quantum Cellular automata (QCA) is a technology developed to replace complementary metal‐oxide‐semiconductor (CMOS) technology that faces increasing challenges due to the miniaturization of CMOS dimensions. The use of multi‐valued QCA is of interest because of its proximity to fuzzy logic, and lower power consumption. A two‐layer quinary system is proposed and the basic logic gates are examined and simulated to confirm the correct performance of the proposed cell. The proposed cell employs two layers because the presence of more than two particles per layer destabilizes the design of logic gates. The proposed Quinary QCA(QuQCA) cell can be implemented in one layer using input and output derives. Simple relationships are proposed to calculate the polarization values and the number and type of layers, so complex quantum computations can be avoided. The quantum power consumption and the proposed cell power consumption of the quinary system are calculated and compared. Finally, we present n ‐valued cells without using quantum computation, and these cells are examined in terms of the number of particles, polarization value, and cell structure. The n ‐level cell can be investigated more easily than other technologies due to its proximity to fuzzy logic and the design of the input, output, and fuzzy membership function. Abstract : Quantum cellular automata (QCA) technology is a proposed technology to replace complementary metal oxide semiconductor (CMOS) technology in logic circuit design. A quinary cell using four particles is presented in which quantum computations and basic gates are presented. Finally, a model is presented which without quantum calculations presents the structure of n ‐value cells and its application in fuzzy logic.